Conceptualizing the Personal Touch: Experiential Knowledge and Gendered Strategies in Community Supervision Work. (June 2019) - Welsh, Megan
Tasked with a fractured institutional mandate of ensuring public safety while facilitating the rehabilitation of their criminalized clients, community supervision workers exercise a considerable amount of discretion in how to achieve these goals. Yet much remains unknown about these workers' strategies for doing so, which are informed by experiential knowledge and social identities—what I call the "personal touch." Drawing on in-depth interviews conducted with California state parole agents and county probation officers as part of a larger ethnographic inquiry of prisoner reentry, I apply a feminist lens to analyze how workers leverage personal aspects of themselves that they value to manage the impossibilities of their work. My findings show how workers employ a personal touch to connect with clients in meaningful ways, but also how these approaches are built on normative assumptions about gender.